Adjustable Pressure Limit Valve Failure During Intraoperative Care: A Case Report. Issue 7 (1st October 2019) - D'Mello, Ajay J.; Raman, Vidya T.; Tobias, Joseph D.
Abstract : One of the many safety features of modern day anesthesia machines is the adjustable pressure limiting (APL) valve. This device regulates pressure within the anesthesia circuit during manual ventilation with the anesthesia bag. We report an unusual case where a crack in the APL valve allowed release of pressure from within the circuit resulting in ineffective bag-valve-mask ventilation of an infant. The appropriate steps to prevent such issues are reviewed, and an algorithm to quickly identify such intraoperative problems is presented.